Enhancing Computational Thinking in Physics Labs: Synergizing STEM Multimedia with Islamic Literacy Integration - Diani, Rahma; Susanti, Agus; Widiawati, Nanda; Velina, Yessy (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This study aims to evaluate the effectiveness of Islamic literacy-based STEM (Science, Technology, Engineering, and Mathematics) multimedia in enhancing students' computational thinking skills in a basic physics practicum course. The research employed a quasi-experimental design with a mixed-methods approach, involving two groups: an experimental group that received instruction through Islamic literacy-based STEM multimedia and a control group that used conventional methods. The instruments used included a computational thinking skills test, designed to measure four primary indicators: abstraction, algorithm, decomposition, and pattern generalization, as well as in-depth interviews to explore students' learning experiences. Quantitative data were analyzed using a t-test to determine significant differences between the two groups, while qualitative data were analyzed thematically. The findings indicated a significant improvement across all computational thinking indicators in the experimental group. Qualitative analysis further revealed that integrating Islamic literacy deepened students' understanding of physics concepts, offering a spiritual context that enriched their learning experiences. These findings suggest that Islamic literacy-based STEM multimedia is not only effective in enhancing computational thinking skills but is also well-suited for educational contexts that integrate technology and spirituality. The implications of this study support the development of a holistic curriculum in STEM education aligned with spiritual values.